Advancing the Competitive Advantage of National Park: Some Actionable Insights for Tourism Management - Rachman, Nono Arief; Susanti, Ervi Nurafliyan; Jubaedah, Dedeh; Rizki, M. Akmal (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Tourism, especially in Ujung Kulon National Park, holds great potential as a leading tourist destination; however, it is hindered by inadequate infrastructure and suboptimal marketing strategies, as well as a decline in tourist confidence due to the tsunami event in 2018. The purpose of this quantitative research is to analyze the influence of Good Corporate Governance (GCG), facilities, digital marketing, and trust on the competitive advantage of tourism in Ujung Kulon. Hypothesis testing using SEM PLS with bootstrapping is employed to analyze the impact of these variables.The research results indicate that GCG does not have a significant effect on competitive advantage, while digital marketing and facilities have a positive impact. Trust, although important, does not moderate the relationship between GCG, digital marketing, or facilities with competitive advantage. This research suggests focusing on the development of infrastructure and digital marketing to enhance the competitiveness of the Ujung Kulon tourism destination.